2021
DOI: 10.1128/spectrum.01202-21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Humoral Immune Response after SARS-CoV-2 Vaccination Using Two Binding Antibody Assays and a Neutralizing Antibody Assay

Abstract: The Siemens severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) IgG (sCOVG; Siemens Healthcare Diagnostics Inc., NY, USA) and Abbott SARS-CoV-2 IgG II Quant (CoV-2 IgG II; Abbott Laboratories, Sligo, Ireland), which are automated, quantitative SARS-CoV-2-binding antibody assays, have been recently launched. This study aimed to evaluate the humoral immune response of BNT162b2 and ChAdOx1 nCoV-19 vaccines using sCOVG and CoV-2 IgG II and compare the quantitative values with the results of the GenScript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 32 publications
1
27
1
1
Order By: Relevance
“…Kang et al reported that seropositive rates after 1st and 2nd inoculation were 66.8% and 98.0% for AZD1222 (AstraZeneca, UK), and 87.5% and 100% for BNT162b2 vaccine [ 22 ]. Nam et al [ 24 ]. also reported that seropositive rates of AZD1222 (AstraZeneca, Cambridge, UK) vaccine were 68.8 and 97.3% after 1st and 2nd inoculation, similar to those reported by Kang et al However, in the case of BNT162b2, the positivity rate after the 1st inoculation was 96.6%, which was significantly higher than that of Kang et al [ 22 ] (87.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al reported that seropositive rates after 1st and 2nd inoculation were 66.8% and 98.0% for AZD1222 (AstraZeneca, UK), and 87.5% and 100% for BNT162b2 vaccine [ 22 ]. Nam et al [ 24 ]. also reported that seropositive rates of AZD1222 (AstraZeneca, Cambridge, UK) vaccine were 68.8 and 97.3% after 1st and 2nd inoculation, similar to those reported by Kang et al However, in the case of BNT162b2, the positivity rate after the 1st inoculation was 96.6%, which was significantly higher than that of Kang et al [ 22 ] (87.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Many papers have reported that AZD1222 (AstraZeneca, UK) has lower vaccine efficacy and/or Nab production rate compared to RNA vaccines [ 22 24 26 27 ]. The most important determinant of producing a high level of Nab is SARS-CoV-2 infection itself.…”
Section: Discussionmentioning
confidence: 99%
“…The value of this study is that there were few studies showing the assessment of concordance by the time point of sample collection taken from the same subjects. From the early period of test development, there were attempts to evaluate the humoral immunity at a specific time point [ 28 ] or serial change over time by comparing multiple tests including our previous study [ 24 ]. However, few studies had evaluated the change up to just before the third dose of a vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…For cPASS, the indicators of neutralization were confirmed for 183, 314, and 253 samples from each point, which were included for comparison analysis, whereas some samples with sCOVG and CoV-2 IgG II results not paired with cPASS were included in the result distribution analysis only. As described in a previous study [ 24 ], the blood samples were collected into Vacuette CAT serum clot activator (Greiner Bio-One, Kremsmunster, Austria) and centrifuged at 1977× g for 10 min, and the serum was aliquoted into two microcentrifuge tubes and stored at −80 °C until measured in four test systems as described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation